Distribution and ecological status of mangroves in the Nias Islands-North Sumatra Province: Distribution and ecological status of mangroves in the Nias Islands - Ahmad Muhtadi; Zulham Apandy Harahap; Ahyar Pulungan; Zufriwandi Siregar; Elisabet Rosevenny Simaremare; Ani Rahmawati; Wilman Nazara; Khairunnisa (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2023)
The Nias Islands are a group of islands located on the west coast of Sumatra. Nias Island is the main and largest island on the West Coast of Sumatra. Information on the distribution and potential status of mangroves in the Nias Islands has been reported, but it is limited to a narrow area and not yet comprehensive throughout the Nias Islands. This study aims to determine the distribution and ecological status of mangroves in the Nias Islands. The research location was divided into two observation areas, namely 15 points on Nias Island and 23 points on the southern part of Nias. The research was carried out in June 2019 and June 2021. Mangrove sampling was carried out using the "spot check" method which refers to Bengen (2004). The results showed that the mangroves found in the Nias Islands consisted of 22 primary mangrove species and 9 secondary mangrove species. Rhizophora apiculata, Rhizophora mucronata, and Xylocarpus granatum are the most abundant mangrove species and are commonly found in the Nias Islands. The thickness of mangroves in the Nias Islands ranges from 15 – 880 m. The density of mangroves found reached 350-4,360 ind/ha. Mangrove cover reaches 0.08-31.62 m2/ha. The results of the analysis of the significant value of mangrove species show that Rhizophora mucronata and Rhizophora apiculata have a large influence and role in the mangrove vegetation community on Nias Island. Mangroves in the Nias Islands are categorized as damaged–good. The good category was found in South Nias, Belukar Bay, and Bengkuang Bay, while the damaged category was found in Lahewa Bay and Dalam Bay